1998
DOI: 10.1099/00207713-48-4-1231
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships among the different phenotypes of Streptococcus dysgalactiae strains

Abstract: The species Streptococcus dysgalactiae was proposed to accommodate a heterogeneous group of streptococci associated with infections in animals and human beings. This taxon is now considered t o include animal isolates of ahaemolytic group C streptococci, previously called 5. dysgalactiae; animal and human isolates of P-haemolytic group C streptococci, previously called '5. equisimilis '; P-haemolytic group L strains associated with infections in animals and, rarely, in humans; and P-haemolytic group G strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
72
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 40 publications
(24 reference statements)
7
72
1
2
Order By: Relevance
“…The species has since been isolated from a variety of other animals including cats, rats, mink, mice, rabbits, and foxes. Studies of human and animal Group G streptococci (GGS) based on whole-cell protein profiles (13) and multilocus enzyme electrophoresis (14) have confirmed that S. canis forms a clear taxonomic group within the pyogenic streptococci. The species appears distinct from the most closely related species that include other pyogenic streptococci associated with humans and animals.…”
mentioning
confidence: 99%
“…The species has since been isolated from a variety of other animals including cats, rats, mink, mice, rabbits, and foxes. Studies of human and animal Group G streptococci (GGS) based on whole-cell protein profiles (13) and multilocus enzyme electrophoresis (14) have confirmed that S. canis forms a clear taxonomic group within the pyogenic streptococci. The species appears distinct from the most closely related species that include other pyogenic streptococci associated with humans and animals.…”
mentioning
confidence: 99%
“…The SDSE is most often resistant to bacitracin [2, 9,18,19], but there are also reports on strains susceptible to that antibiotic [13,14,18,21,27]. The susceptibility to bacitracin is typical of SDSE strains with a group L antigen [21,27], but susceptible SDSE isolates with a group A antigen have been described as well [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility to bacitracin is typical of SDSE strains with a group L antigen [21,27], but susceptible SDSE isolates with a group A antigen have been described as well [13,14]. Typically, SDSE strains produce no L-pyrrolidonyl arylamidase, and display a negative result of the Voges-Proskauer test, positive result of β-glucuronidase and negative result of α-and β-galactosidase test [9,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations